The compactificability classes of certain spaces - Martin Maria Kovár (International Journal of Mathematics and Mathematical Sciences)
We apply the theory of the mutual compactificability to some spaces, mostly derived from the real line. For example, any noncompact locally connected metrizable generalized continuum, the Tichonov cube without its zero point Iℵ0\{0}, as well as the Cantor discontinuum without its zero point Dℵ0\{0} are of the same class of mutual compactificability as ℝ.